Evaluation of end-seasonal vitamin d, plasma lipid and other biochemical measurements in professional football players: The case of sivas province in turkey - Sariakcali, Baris; Ceylan, Levent; Elioz, Murat (Progress in Nutrition, 2020)
Study Objectives: This study aimed to evaluate the end-seasonal blood lipids and some metabolic parameters of the athletes who play football professionally. Methods: Thirty six male professional footballers playing in the Super League and TFF 2nd League (Turkish Football Federation Second League) in Sivas province, aged between 19 and 32 (mean age 23.33±3.49 years), participated in this research. The athlete age of the players participating in the study is 11.66±3.72 years. In addition, the athletes participating in the study regularly train 90-120 minutes a day, 6-7 times a week, and approximately 11 months a year. All measurements and venous blood sampling of the participants were collected between 09:00 and 10:00 in the morning after 12-hour fasting in June. The biochemical tests of the participants were obtained with the Beckman DXC-800 model autoanalyzer in the Private Clinical Biochemistry Laboratory and the enzymatic-colorimetric method. IBM SPSS Statistics 24 package software was used to analyze the obtained data. Descriptive statistics of the obtained data were given as mean and standard deviation. Results: Albumin, ALP, ALT, AST, B12 vitamin, Ca, Phosphorus, Creatinine, Mg, Free T3, Sodium, TSH, Ferritin, Folic Acid, Potassium, Free T4, and Uric Acid values of the participant athletes were found to be within normal limits. Conclusion: it was concluded that the HDL cholesterol levels of the smoker athletes were low due to smoking and vitamin D values were low in professional football players.